Minimal Circular Nearly Strongly Balanced Repeated Measurements Designs in Unequal Period Sizes: Repeated Measurements Designs in Unequal Period Sizes - Rasheed, H. M. Kashif; Khan, Hafsa; Ahmed, Rashid; Jamal, Farrukh (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2022)
In this article, some series are developed to generate circular nearly strongly balanced repeated measurements designs in periods of three different sizes when p3 (smallest period size) = 2 through method of cyclic shifts (Rule II). These designs with varied period sizes have diversified applications, e.g. medicine, pharmacology, animal sciences and psychology. These designs are mainly used to balance the first order residual effect. Our proposed designs possessat least 98% efficiency of separability, therefore these designs are highly efficient to estimate the residual effects and direct effects independently.